Clinical Trials in Rheumatology - Mueller, Ruediger. (Springer London : Imprint: Springer, 2013)
A huge number of therapeutic studies has been published in rheumatology and clinical immunology. This number grows substantially by the year. As such, it becomes increasingly difficult to keep track of this multitude of studies and the ensuing therapeutic trends. Further to this, a particular study can be referred to in a variety of ways, either as a shortened version of the title or an acronym, adding to the confusion. The book Clinical Trials in Rheumatology, Second Edition, provides an updated summary of the important studies in the field for easy reference. Every study is shown with name, acronym (if in existence), authors, complete citation, study design, and a short overview of the trial's data and main conclusions. An acronym finder is supplied at the beginning of the book. This book is a valuable reference tool for rheumatologists and other clinical specialties, as well as for research scientists interested in immunomodulatory and selected other drug therapies in rheumatologic diseases.